Subthreshold conditions as precursors for full syndrome disorders: A 15-year longitudinal study of multiple diagnostic classes - Shankman, Stewart A. (2009)
BACKGROUND: There has been increasing interest in the distinction between subthreshold and full syndrome disorders and specifically whether subthreshold conditions escalate or predict the onset of full syndrome disorders over time. Most of these studies, however, examined whether a single subthreshold condition escalates into the full syndrome form of that disorder. Equally important, though, is whether subthreshold conditions are likely to develop other full syndrome disorders and whether these associations are maintained after adjusting for comorbidity. METHODS: A 15-year longitudinal study of subthreshold psychiatric conditions was conducted with 1505 community drawn young adults. We examined whether 1) subthreshold major depression, bipolar, anxiety disorders, alcohol use, substance use, conduct disorder and/or ADHD were precursors for the corresponding (homotypic) full syndrome disorder; 2) subthreshold conditions were precursors for other (heterotypic) FS disorders; and 3) these homotypic and heterotypic precursors persisted after adjusting for comorbidity. RESULTS: Subthreshold major depression, anxiety, alcohol use, substance use, and conduct all escalated into their corresponding full syndrome and nearly all homotypic developments were maintained after adjusting for comorbid subthreshold and FS conditions. Many heterotypic associations were also observed and most remained after controlling for comorbidity, particularly among externalizing disorders (e.g., alcohol, substance, conduct/antisocial personality disorder). CONCLUSIONS: Many subthreshold conditions have predictive validity as they may represent precursors for full syndrome disorders. Alternatively, dimensional conceptualizations of psychopathology which include these more minor conditions may yield greater validity. Subthreshold conditions may represent good targets for preventive interventions.